Scooby-Doo meets Batman [videorecording (DVD)] - Hanna, William, 1910-2001; Barbera, Joseph; Brewer, Jameson; Dagenais, Tom; Flippen, Ruth; Jaffe, Nicole; Kasem, Casey; Messick, Don; North, Heather; Welker, Frank; Stephenson, John; Butler, Daws; et al. (Warner Bros. Family Entertainment., 2002)
The action begins as The Joker and The Penguin try to cash in on a crooked counterfeiting scheme only to be foiled by the Dynamic Trio of Batman, Robin and Scooby-Doo! But The Joker and The Penguin return to try and steal a flying suit until Scooby-Doo and the gang prove that with a little help they have what it takes to bring the sky-high scoundrels back to Earth.